Asymmetric total synthesis of eicosanoid - Mohapatra, Debendra K.; Yellol, G. S. (Arkivoc, 2005)
An asymmetric total synthesis of eicosanoid 4 starting from 2,2- dimethyl-( R)- 1,3- dioxolane-4- carbaldehyde is described. The key steps involved for the synthesis include modified Simmons-Smith cyclopropanation, stereoselective reduction, ring-closing metathesis (RCM) and Nozaki- Hiyama- Kishi coupling reaction.
Keywords: cyclopropanation; eicosanoid; lipoxygenase inhibitors; Ring-closing metathesis; Stereoselective